Responses of α-amylase and protease activity to chemical agents and metallic salts in barley seeds (Hordeum vulgare L.) - Amin Hossain; Umma Fatema Shahjadee; Abu Tareq Mohammad Abdullah; Mohammad Nazrul Islam Bhuiyan; Anjum Zerin Rupa (Heliyon)
In modern agriculture, the enzymes inhibition by chemical agents and environmental pollutants accounts for a significant threat to crop health and productivity. Enzymes play a crucial role in maintaining homeostasis in the metabolic processes that sustain life. Understanding what regulates enzyme activity is crucial for many scientific and industrial endeavors. The purpose of this research work was to examine how different chemical agents, and metallic salts affected the activity of two important food enzymes like α-amylase and protease in barley. These studies compared the effects of several chemical treatments applied to barley seeds, including urea, ethylenediaminetetraacetic acid (EDTA), acetic acid, and a wide range of metallic salts. To determine the impact of each chemical on the stability of α-amylase and protease enzyme activity using standard assay procedures. The activities of α-amylase and protease were inhibited by increasing urea concentration, eventually eliminating them at 8 M urea. The enzymes lost their activities completely at 0.50 M EDTA. Treatment with higher acetic acid concentrations decreased their activities, but they retained 20.46 ± 1.06 % and 17.38 ± 1.09 % after treating with 20 % acetic acid. The application of CaCl2 led to a progressive increase for both the enzyme activities, but the maximum increases were observed 137.26 ± 1.42 % and 135.65 ± 1.17 % due to 0.50 M Ca2+. In the presence of Mn2+ and Mg2+ salts, enzyme activity increased notably. In contrast to K+ and Na+, which have negligible or no inhibitory effects but Zn2+, Cu2+, and Fe2+ considerably reduce the activity of both enzymes. According to the findings, the present research could be created with the scope of potentially identifying ways to maintain their activity for agricultural, industrial and also scientific applications.